Comparative Transcriptome Analysis between Gynoecious and Monoecious Plants Identifies Regulatory Networks Controlling Sex Determination in Jatropha curcas - Chen, Mao-Sheng; Pan, Bang-Zhen; Fu, Qiantang; Tao, Yan-Bin; Martínez-Herrera, Jorge; Niu, Longjian; Ni, Jun; Dong, Yuling; Zhao, Mei-Li; Xu, Zeng-Fu (Frontiers in Plant Science, 2017)
Most germplasms of the biofuel plant Jatropha curcas are monoecious. A gynoecious genotype of J. curcas was found, whose male flowers are aborted at early stage of inflorescence development. To investigate the regulatory mechanism of transition from monoecious to gynoecious plants, a comparative transcriptome analysis between gynoecious and monoecious inflorescences were performed. A total of 3,749 genes differentially expressed in two developmental stages of inflorescences were identified. Among them, 32 genes were involved in floral development, and 70 in phytohormone biosynthesis and signaling pathways. Six genes homologous to KNOTTED1-LIKE HOMEOBOX GENE 6 (KNAT6), MYC2, SHI-RELATED SEQUENCE 5 (SRS5), SHORT VEGETATIVE PHASE (SVP), TERMINAL FLOWER 1 (TFL1), and TASSELSEED2 (TS2), which control floral development, were considered as candidate regulators that may be involved in sex differentiation in J. curcas. Abscisic acid, auxin, gibberellin, and jasmonate biosynthesis were lower, whereas cytokinin biosynthesis was higher in gynoecious than that in monoecious inflorescences. Moreover, the exogenous application of gibberellic acid (GA3) promoted perianth development in male flowers and partly prevented pistil development in female flowers to generate neutral flowers in gynoecious inflorescences. The arrest of stamen primordium at early development stage probably causes the abortion of male flowers to generate gynoecious individuals. These results suggest that some floral development genes and phytohormone signaling pathways orchestrate the process of sex determination in J. curcas. Our study provides a basic framework for the regulation networks of sex determination in J. curcas and will be helpful for elucidating the evolution of the plant reproductive system.